2021
DOI: 10.3390/antiox10091406
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Polyphenols Characterization of Four Monovarietal Grape Pomaces from Salento (Apulia, Italy)

Abstract: The wine industry annually produces millions of tons of by-products rich in polyphenolic compounds that can be reused as secondary raw material in the food, cosmetic and pharmaceutical industries. The purpose of this work was to describe the presence of nutraceutical compounds and to evaluate the antioxidant activity of pomaces from three Apulian (South-Italy) grape varieties (Negroamaro, Malvasia di Lecce and Primitivo) and to compare them with one of the most cultivated wines in Europe (Cabernet Sauvignon). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 56 publications
6
26
1
Order By: Relevance
“…Fourteen flavan-3-ols, monomers, and trimers of (-)-epicatechin and (+)-catechin; 10 flavonols, derivatives of quercetin and kaempferol; 1 hydroxycinnamic acid, a derivative of p -coumaric acid; and 13 anthocyanins, 3- O -glycosides of malvidin, petunidin, cyanidin, peonidin, and delphinidin being the major components, were identified in the extract. These findings were in accordance with previously reported work, where anthocyanins were also the main compounds found in red grape skin extracts, and among them, Mv-3- O -glc was the most important [ 29 , 30 ]. As for the other compounds, the most abundant were reported to be phenolic acids, flavan-3-ols, and flavonols [ 31 ].…”
Section: Resultssupporting
confidence: 93%
“…Fourteen flavan-3-ols, monomers, and trimers of (-)-epicatechin and (+)-catechin; 10 flavonols, derivatives of quercetin and kaempferol; 1 hydroxycinnamic acid, a derivative of p -coumaric acid; and 13 anthocyanins, 3- O -glycosides of malvidin, petunidin, cyanidin, peonidin, and delphinidin being the major components, were identified in the extract. These findings were in accordance with previously reported work, where anthocyanins were also the main compounds found in red grape skin extracts, and among them, Mv-3- O -glc was the most important [ 29 , 30 ]. As for the other compounds, the most abundant were reported to be phenolic acids, flavan-3-ols, and flavonols [ 31 ].…”
Section: Resultssupporting
confidence: 93%
“…Ten flavan-3-ols ((−)-epicatechin and (+)-catechin monomers and trimers); 11 flavanols (derivatives of quercetin, kaempferol and isorhamnetin); 1 dihydroflavanol; 1 hydroxycinnamic acid derivative of p -coumaric acid; 1 hydroxybenzoic acid; and 13 anthocyanins (3- O -glucosides of delphinidin, cyanidin, petunidin, peonidin, and malvidin) were identified in GE. These findings are in line with previous data reporting anthocyanins as the main components of extracts from red grape skin, with Mv-3- O -glc being the most abundant [ 20 , 21 ]. Among the other components, phenolic acids, flavan-3-ols and flavanols have been reported as the most representative classes [ 22 ].…”
Section: Resultssupporting
confidence: 93%
“…The values obtained for the TPC are in good agreement with the ones reported by other authors when levels between 30 and 70 mg/g were reported [58][59][60][61]. The high value obtained in the present study are for the lyophilized extract in ethanol/water.…”
Section: Discussionsupporting
confidence: 93%